Patterns of Antihistamin and Corticosteroids Usage In Dermatitis Patients At Primary Public Health Center in Jombang: Pola Penggunaan Antihistamin dan Kortikosteroid Pada Pasien Dermatitis di Puskesmas Kabupaten Jombang - Shofiatul Fajriyah; Dea Justisia Ayu Nandya; Erni Anikasari; Fenita Shoviantari (Akademi Farmasi Surabaya, 2023)
Dermatitis or eczema is a form of the condition in which the layers of the skin (epidermis and dermis) have general inflammation which is usually influenced by endogenous and exogenous factors causing clinical abnormalities in the form of polymorphic efflorescence (erythema, edema, papules, vesicles, scales, lichenification) and itching complaint. This study simed to determine the treatment pattern given to patients with atopic dermatitis and contact dermatitis at the Jelakombo Health Center Jombang. This was an observational study with retrospective data collection. The data sourced used was existing medical records from January to December 2020. Data analysis was carried out descriptively with purposive sampling. The results showed that the most common dermatitis patients were atopic dermatitis (34%) which mostly treated with CTM+Dexamethasone. Patients with allergic contact dermatitis were 38 patients (38%), the most common drug regimen to manage it was Cetirizine+Hydrocortisone ointment. There were 28 patients (28%) with irritant contact dermatitis, which mostly treated with Cetirizine+Hydrocortisone Ointment followed by CTM + Dexamethasone. This study concluded that the drug regimen for the three types of dermatitis was almost the same, namely a combination of oral and topical antihistamines and corticosteroids. The antihistamines used were first-generation antihistamines (CTM) and second-generation (Cetirizine and Loratadine). Further assessment related to whether the sedation effect was wanted or it was disturbing side effect is needed. The widely used oral corticosteroid was dexamethasone, which is a high-potency corticosteroid, so its use must be judicious. Topical corticosteroids were hydrocortisone ointments that include low potency topical corticosteroids which are the first line of atopic dermatitis and allergic contact dermatitis.